Corrected Fire Perimeters of Alaska's National Wildlife Refuges ... - Carson A Baughman (U.S. Geological Survey, 2024)
This data package includes 481 geospatial vector polygons of historic fire perimeters associated with National Wildlife Refuges in Alaska. These polygons, originally held within the Alaska Large Fire Database (ALFD), were reviewed and found to have geospatial inaccuracies with respect to the fire they represent. They were corrected and updated based on a variety of remote sensing resources; the Monitoring Trends in Burn Severity (MTBS) database (https://www.mtbs.gov/viewer/index.html), geospatial rasters of historic fire activity derived from Landsat 1-9 imagery in the Google Earth Engine(https://earthengine.google.com) environment, and historical air photos acquired through EarthExplorer (https://earthexplorer.usgs.gov/). Wildfire records occurring within Alaska Wildlife Refuge units and considered for necessary updates, spanned the 1943-2022 time period and comprised 1,229 recorded fires. After reviewing all fire records, 400 fire perimeters were updated and 81 previously unrecorded fires were added to the ...